Inquiry survey regarding awareness of the faculty members about curriculum - Piryani, Rano Mal; Piryani, Suneel; Deo, Gopendra Prasad (Journal of Chitwan Medical College, 2018)
Introduction: The main objectives of this inquiry survey were to get information from the participants of 4th, 5th & 6th teachers training workshop about the types of curriculum implemented in medical colleges in Nepal and whether they possess the copy of curriculum and study it. Methods: Inquiry survey regarding awareness of the faculty members about curriculum was done during 4th, 5th & 6th teachers training workshop held in February 27–March 3, 2016, September 5–10, 2016, and March 25- 30, 2017 respectively at Health Professionals’ Education and Research Center, Chitwan Medical College, Bharatpur, Nepal. Questionnaire was developed and piloted in 3rd teachers training workshop held in July 26–31, 2015 and subsequently used in 4th,5th & 6th workshop for inquiry survey. Results: Around 20% participants didn’t respond to question 1 (What types of curriculum is being implemented in medical colleges in Nepal?) and 2 (whether they possess the copy of curriculum and study it?), while around 11% and 18% had no idea on question 1 & 2 respectively. Response of around 20% participants on question 1 & 2 was acceptable while response of around 48% and 42% participants on question 1 & 2 respectively was vague. Two of 45 participants possessed the copy of curriculum while seven of 43 participants seen the curriculum. All participants agreed to have copy of curriculum and understand it. Conclusion: Majority of the participants didn’t aware of the curriculum, so authors recommended to management to provide copy of curriculum to faculty members and students too.